MODEL PELAKSANAAN DISEMINASI INFORMASI PENGINDERAAN JAUH BERBASIS TEKNOLOGI TERBUKA - Sarno, Sarno (Institut Teknologi Sepuluh Nopember, 2016)
National Earth Observation System at the Remote Sensing Application Center organize the functions of remote sensing information dissemination to the user. Space Law Number 21 of 2013 Article 22, Paragraph 1, mandates that the use of data and dissemination of remote sensing information shall be based on the guidelines set by the Institution. This research aims to analyze reference implementation of remote sensing information dissemination. The method used in this study is prototyping with an open technology. Stages of research include the identification of technology components and evaluation of the general architecture to simplify the development, design models and implementation of the system by reforming, repeatedly testing and integration of open source software. The results showed that the model or reference implementation has been successfully implemented and tested through prototypes. Application of the prototype into a fully operational system can be developed at low cost and user friendly interface.